Modeling players' scanning activity in football - Pokolm, M.; Rein, R.; Müller, D.; Nopp, S.; Kirchhain, M.; Aksum, K. M.; Jordet, G.; Memmert, D. (Journal of Sport & Exercise Psychology, 2022)
The purpose of this study was to develop and test models of scanning activity in football. Gibson`s ecological approach of visual perception and exploratory activity provided the theoretical framework for the models. The video-based data analysis consisted of 17 selected matches and 239 players of the Union of European Football Associations (UEFA) U17 and U19 European Championship 2018 and the UEFA U17 and U21 European Championship 2019. The results showed a positive relation between scanning frequency and successful passes, as well as changes in body orientation. Scanning frequency was also related to a player`s appearances in national teams and to opponent pressure. Opponent pressure had a large effect on pass result and the player`s body orientation. Previous research on the relation between scanning frequency and performance was extended by several contextual predictors. Future research should focus on gaining a deeper understanding of the relation between scanning frequency and further contextual variables related to scanning.